Holocene tephrostratigraphy in Vestfirðir, NW Iceland. (6th September 2018) - Gudmundsdót tir, Esther Ruth; Schomacker, Anders; Brynjólfsson, Skafti; Ingólfsson, Ólafur; Larsen, Nicolaj K.
ABSTRACT: We present a tephra stratigraphical and tephrochronological record from eight lakes in Vestfirðir, NW Iceland. About 50 tephra units have been identified, representing nearly 30 eruptive events originating from five volcanic systems: Hekla, Katla, Snæfellsjökull, Grímsvötn and Veiðivötn‐Bárðarbunga. Most of the tephra layers originate from Grímsvötn, although there is a prominent presence of andesitic to basaltic tephra layers from Hekla in the record. We propose that the previously described Brattihjalli tephra is actually the 6060‐year‐old Hekla Ö tephra marker layer, recording a more north‐westerly dispersal than before and providing new correlation possibilities across Iceland. Thus, the Hekla Ö tephra covers as large an area in Iceland as the Hekla 5, Hekla 4, Hekla 3 and Hekla 1104 tephra layers, emphasizing its importance as a chronological marker. The tephra markers Hekla 1693, V877/Settlement layer, Sn‐1, Hekla 3 and Hekla 4 have been found and, additionally, our study identifies four potential tephra markers, the Katla D1 ∼2750 cal aBP, Katla D2 ∼3700 cal aBP, Reykjarfjörður tephra ∼8800 cal aBP and Dagverðardalur tephra ∼9300–9500 cal aBP . Our data reveal several new tephra layers in Vestfirðir, including chronological markers important for dating and correlation.